STUDI EKSPERIMENTAL PERFORMANSI TURBIN SAVONIUS DENGAN PENAMBAHAN PANEL SURYA 100 WP POLYCRISTALLINE DI PESISIR PANTAI KABUPATEN DEMAK TERHADAP DAYA LISTRIK YANG DIHASILKAN - Riza Ashari; Herman Saputro; Husin Bugis (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2020)
The use of fossil fuels in the form of petroleum, coal and natural gas in the long term as conventional power plants causes the scarcity of these fuels in the future. Then the use of new renewable energy such as wind and solar energy must be optimized. In Indonesia, both of these energies have the potential to be environmentally friendly power plants. Experimental research conducted on the coast of Demak Regency aims to determine the potential of wind and solar energy there and the use of both energy as pond lighting. The concept of a combination of solar panels and savonius turbines can produce complementary energy. During the day the battery charging is obtained from a combination of solar panels and savonius turbines while at night the Savonius turbine will still produce electricity. The S-type savonius turbine made from galvalum is mounted on a 6 m tall tower while the 100 WP solar panel is mounted beside it with a 90 slope. This penelitian use expermental methods. Data collection of wind speed, light intensity, electric current, and electric voltage is carried out periodically 20 minutes at 06.20 s.d. 17.20 Western Indonesian Time. Electrical power is obtained by multiplying curr Data analysis in this study uses quantitative descriptive analysisent and voltage. The combination produces enough electricity for lighting a pond in the village of Berahan Kulon, Kecamatan Wedung. The power generated from a combination of hybrid plants can reach 46,2 watts with the intensity of sunlight of 125000 luxmeter and constant wind speed around 2 to 4 m / s. From these results, a combination of turbine savonius and solar panels is more optimal compared to a stand-alone savonius turbine.